L1 cell adhesion molecule overexpression in hepatocellular carcinoma associates with advanced tumor progression and poor patient survival - Guo Xiaodong; Xiong Lu; Zou Lin; Sun Ting; Zhang Jing; Li Hanwei; Peng Ruiyun; Zhao Jingmin (BMC, 2012)
Abstract Objective L1 cell adhesion molecule (L1CAM), as a member of the immunoglobulin superfamily, has recently been observed in a variety of human malignancies. However, no data of L1CAM are available for hepatocellular carcinoma (HCC). The aim of this study was to investigate the expression of L1CAM in HCC and determine its correlation with tumor progression and prognosis. Methods One-hundred and thirty HCC patients who had undergone curative liver resection were selected and immunohistochemistry, Western blotting, and quantitative real time polymerase chain reaction (Q-PCR) were performed to analyze L1CAM expression in the respective tumors. Results Immunohistochemistry, Western blotting, and Q-PCR consistently confirmed the overexpression of L1CAM in HCC tissues compared with their adjacent nonneoplastic tissues at both protein and gene level (both P <0.01). Additionally, the high expression of L1CAM was significantly associated with advanced tumor stage (P = 0.02) and advanced tumor grade (P = 0.03), respectively. Moreover, HCC patients with high L1CAM expression were significantly associated with lower 5-year overall survival (P <0.01) and lower 5-year disease-free survival (P <0.01), respectively. The Cox proportional hazards model further showed that L1CAM over-expression was an independent poor prognostic factor for both 5-year disease-free survival (P = 0.02) and 5-year overall survival (P = 0.008) in HCC. Conclusion Our data suggest for the first time that L1CAM expression in HCC was significantly correlated with the advanced tumor progression and was an independent poor prognostic factor for both overall survival and disease-free survival in patients with HCC. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1970024872761542